Increased left ventricular trabeculation in highly trained athletes: do we need more stringent criteria for the diagnosis of left ventricular non-compaction in athletes?. Issue 6 (7th February 2013) - Gati, Sabiha; Chandra, Navin; Bennett, Rachel Louise; Reed, Matt; Kervio, Gaelle; Panoulas, Vasileios F; Ghani, Saqib; Sheikh, Nabeel; Zaidi, Abbas; Wilson, Matthew; Papadakis, Michael; Carré, Francois; et al.
Abstract : Objective: To investigate the prevalence and significance of increased left ventricular (LV) trabeculation in highly trained athletes. Design: Cross sectional echocardiographic study. Setting: Sports cardiology institutions in the UK and France. Subjects: 1146 athletes aged 14–35 years (63.3% male), participating in 27 sporting disciplines, and 415 healthy controls of similar age. The results of athletes fulfilling conventional criteria for LV non-compaction (LVNC) were compared with 75 patients with LVNC. Main outcome measure: Number of athletes with increased LV trabeculation and the number fulfilling criteria for LVNC. Results: Athletes displayed a higher prevalence of increased LV trabeculation compared with controls (18.3% vs 7.0%; p≤0.0001) and 8.1% athletes fulfilled conventional criteria for LVNC. Increased LV trabeculation were more common in athletes of African/Afro-Caribbean origin. A small proportion of athletes (n=10; 0.9%) revealed reduced systolic function and marked repolarisation changes in association with echocardiographic criteria for LVNC raising the possibility of an underlying cardiomyopathy. Follow-up during the ensuing 48.6±14.6 months did not reveal adverse events. Conclusions: A high proportion of young athletes exhibit conventional criteria for LVNC highlighting the non-specific nature of current diagnostic criteria if applied to elite athletic populations. Further assessment of such athletes should be confined to the small minority that demonstrate low indices of systolic function and marked repolarisation changes.